Yeast functional screen to identify genes conferring salt stress tolerance in Salicornia europaea - Nakahara, Yoshiki; Sawabe, Shogo; Kainuma, Kenta; Katsuhara, Maki; Shibasaka, Mineo; Suzuki, Masanori; Yamamoto, Kosuke; Oguri, Suguru; Sakamoto, Hikaru (Frontiers in Plant Science, 2015)
Salinity is a critical environmental factor that adversely affects crop productivity. Halophytes have evolved various mechanisms to adapt to saline environments. Salicornia europaea L. is one of the most salt-tolerant plant species. It does not have special salt-secreting structures like a salt gland or salt bladder, and is therefore a good model for studying the common mechanisms underlying plant salt tolerance. To identify candidate genes encoding key proteins in the mediation of salt tolerance in S. europaea, we performed a functional screen of a cDNA library in yeast. The library was screened for genes that allowed the yeast to grow in the presence of 1.3 M NaCl. We obtained three full-length S. europaea genes that confer salt tolerance. The genes are predicted to encode (1) a novel protein highly homologous to thaumatin-like proteins, (2) a novel coiled-coil protein of unknown function, and (3) a novel short peptide of 32 residues. Exogenous application of a synthetic peptide corresponding to the 32 residues improved salt tolerance of Arabidopsis. The approach described in this report provides a rapid assay system for large-scale screening of S. europaea genes involved in salt stress tolerance and supports the identification of genes responsible for such mechanisms. These genes may be useful candidates for improving crop salt tolerance by genetic transformation.